(7x-3)(7x+3)=0

Simple and best practice solution for (7x-3)(7x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-3)(7x+3)=0 equation:


Simplifying
(7x + -3)(7x + 3) = 0

Reorder the terms:
(-3 + 7x)(7x + 3) = 0

Reorder the terms:
(-3 + 7x)(3 + 7x) = 0

Multiply (-3 + 7x) * (3 + 7x)
(-3(3 + 7x) + 7x * (3 + 7x)) = 0
((3 * -3 + 7x * -3) + 7x * (3 + 7x)) = 0
((-9 + -21x) + 7x * (3 + 7x)) = 0
(-9 + -21x + (3 * 7x + 7x * 7x)) = 0
(-9 + -21x + (21x + 49x2)) = 0

Combine like terms: -21x + 21x = 0
(-9 + 0 + 49x2) = 0
(-9 + 49x2) = 0

Solving
-9 + 49x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 49x2 = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 49x2 = 0 + 9
49x2 = 0 + 9

Combine like terms: 0 + 9 = 9
49x2 = 9

Divide each side by '49'.
x2 = 0.1836734694

Simplifying
x2 = 0.1836734694

Take the square root of each side:
x = {-0.428571429, 0.428571429}

See similar equations:

| T*7=5 | | 12/7=x/10 | | (x-1)+(3x+1)+(3x)=56 | | 3x+120=9x-12 | | x-1+3x+1+3x=56 | | -32=-6x-8 | | x+1/5=x+5/7 | | 4(2y+1)=(12-y) | | y=x^2-4x-28 | | 260=-u+123 | | -y+233=171 | | 5x+3x=5y-3y | | 15-u=283 | | -6(2x-1)=12x-6 | | x(3-8)=3x-8x | | 2q=1-7 | | (x-5)*6=54 | | 2x-3(2/x) | | 4x^2+3x=18 | | z^3-(4-3i)z^2+(9-2i)z-2+11i=0 | | 2[3lnx-ln(x+1)-ln(x-1)]= | | 3x=(20/7)-x | | (4+7i)(5-3i)= | | 20-5x=32+7x | | 7(7x-5)= | | 15=3xy | | 5x^2+3y^2=0 | | 10x^2+3y^2=2 | | 12n+4n=16n^2 | | 12n+4n=16n | | 12n+4n=16 | | 3x+50=2x+10 |

Equations solver categories